A unified multiple-level cache for high performance storage systems. (15th November 2007) - He, Xubin (Ben); Kosa, Martha J.; Scott, Stephen L.; Engelmann, Christian
Multi-level cache hierarchies are widely used in high-performance storage systems to improve I/O performance. However, traditional cache management algorithms are not suited well for such cache organisations. Recently proposed multi-level cache replacement algorithms using aggressive exclusive caching work well with single or multiple-client, low-correlated workloads, but suffer serious performance degradation with multiple-client, high-correlated workloads. In this paper, we propose a new cache management algorithm that handles multi-level buffer caches by forming a unified cache (uCache), which uses both exclusive caching in L2 storage caches and cooperative client caching. We also propose a new local replacement algorithm, Frequency Based Eviction-Reference (FBER), based on our study of access patterns in exclusive caches. Our simulation results show that uCache increases the cumulative cache hit ratio dramatically. Compared to other popular cache algorithms, such as LRU, the I/O response time is improved by up to 46% for low-correlated workloads and 53% for high-correlated workloads.